Union of the Comoros : Poverty Reduction and Growth Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2010)
A poverty profile for the Comoros has been established based on the latest poverty data (EIM 2004). The data indicate that monetary poverty is still widespread in the Comoros. For the overall country, the incidence of poverty at the household level was estimated at 36.9 percent in 2004. Three socioeconomic groups account for nearly two-thirds of national poverty: farmers' households (30.2 percent), unprotected wage earners' households (15.8 percent), and households headed by an inactive person (19.6 percent).